Further notes on the archaeological object. (11th May 2018) - Edgeworth, Matt
Abstract : Assaf Nativ argues that it is time to deepen and broaden our understanding of the archaeological object, and to make it more explicit. I find the general argument of the paper compelling. Following on from the insights contained therein, it seems to me that there are three principal aspects of the archaeological object that urgently need to be reappraised: (1) temporal range, (2) spatial scale and (3) ecological effectivity.